2020
DOI: 10.3390/pathogens9050406
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding of the Genus Culicoides (Diptera: Ceratopogonidae) in Austria—An Update of the Species Inventory Including the First Records of Three Species in Austria

Abstract: Ceratopogonidae are small nematoceran Diptera with a worldwide distribution, consisting of more than 5400 described species, divided into 125 genera. The genus Culicoides is known to comprise hematophagous vectors of medical and veterinary importance. Diseases transmitted by Culicoides spp. Such as African horse sickness virus, Bluetongue virus, equine encephalitis virus (Reoviridae) and Schmallenberg virus (Bunyaviridae) affect large parts of Europe and are strongly linked to the spread and abundance of its v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…DNA barcoding is a system that uses short, standard gene sequences as inter-species labels to perform rapid, accurate, and automatic species identification [ 7 , 8 , 9 ]. The mitochondrial cytochrome c oxidase subunit I ( COI ) gene sequence is a powerful marker for the discrimination of evolutionary divergence because of its female inheritance, high evolutionary rate, and stable gene content [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding is a system that uses short, standard gene sequences as inter-species labels to perform rapid, accurate, and automatic species identification [ 7 , 8 , 9 ]. The mitochondrial cytochrome c oxidase subunit I ( COI ) gene sequence is a powerful marker for the discrimination of evolutionary divergence because of its female inheritance, high evolutionary rate, and stable gene content [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barcoding was the only effective method to differentiate sibling species, such as C. obsoletus and C. scoticus, when morphological identification of specimens was difficult [ 45 ]. Molecular methods, in combination with morphological determination, have been used to verify identity of described species in Sweden [ 46 ] and Tunisia [ 47 ], to discover new species [ 48 , 49 ], study the species composition [ 50 ] and screen the potential BTV vectors in the obsoletus complex in France [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…paradoxalis. ; C. boyi; C. selandicus; and C. kalix [51]. The faunistic entomological papers published in Slovakia [33,41,43,47] reported that the Culicoides subgenus contained the following 5 species of biting midges: C. pulicaris, C. punctatus, C. newsteadi, C. lupicaris, and C. bysta.…”
Section: Discussionmentioning
confidence: 99%
“…Biting midges of the Culicoides subgenus include 14 species, i.e., C. pulicaris ; C. lupicaris ; C. impunctatus ; C. punctatus ; C. grisescens ; C. newsteadi ; C. flavipulicaris ; C. fagineus ; C. subfagineus ; C. bysta ; C. paradoxalis. ; C. boyi ; C. selandicus ; and C. kalix [ 51 ]. The faunistic entomological papers published in Slovakia [ 33 , 41 , 43 , 47 ] reported that the Culicoides subgenus contained the following 5 species of biting midges: C. pulicaris , C. punctatus , C. newsteadi , C. lupicaris , and C. bysta .…”
Section: Discussionmentioning
confidence: 99%